Growth of body size (body height and body weight) and somatotype in 363 girls and 299 boys aged 4 to 20 years of ethnic Javanese lived in Magelang Regency Indonesia were studied cross-sectionally. Over half of them were categorized in the well-off family, therefore underweight or underfat prevalence in our subjects was low (14.3%) but overweight and obesity prevalence was also low (14%). They were shorter and lighter than reference children from U.S., Japan and Yogyakarta but they improved when - TETRI WIDIYANI; BAMBANG SURYOBROTO; SRI BUDIARTI; ALEX HARTANA (HAYATI Journal of Biosciences, 2011)
Growth of body size (body height and body weight) and somatotype in 363 girls and 299 boys aged 4 to 20 years of ethnic Javanese lived in Magelang Regency Indonesia were studied cross-sectionally. Over half of them were categorized in the well-off family, therefore underweight or underfat prevalence in our subjects was low (14.3%) but overweight and obesity prevalence was also low (14%). They were shorter and lighter than reference children from U.S., Japan and Yogyakarta but they improved when compared with those of the same ethnic of Bantul and with the different ethnic of rural India. There was a clear age-related change of their somatotype. At age 4 years, the physique of children subjects in both sexes is found to be mesomorph-endomorph. Thereafter it is transformed into ectomorphic-endomorph in girls and to mesomorph-ectomorph in boys at the age of 20 years. In girl subjects, the onset of puberty was characterized by an acceleration of endomorphy component at age 8 years. While in our boys it was characterized by an acceleration of ectomorphy since age 9 years. The different growth pattern of somatotype components showed that the use of BMI as an indicator of fatness in children should be reassessed.